The Mongol Invasion of Hungary in Its Eurasian Context - Laszlovszky, József; Nagy, Balázs; B. Szabó, János; Uhrin, Dorottya (Historical Studies on Central Europe, 2023)
This report gives an account of the historiography of the Mongol invasion of Hungary in 1241–1242, and the ongoing research of the project “The Mongol Invasion of Hungary in its Eurasian Context.” The research has been carried out by an interdisciplinary team comprising representatives of diverse academic institutions and fields. The primary objective of the project was to reassess existing scholarship by comparing it with the findings of the project team members, ultimately generating new scholarly insights. The team members concentrated on various aspects, including archaeology, military history, and the short- and long-term impacts of the Mongol military invasions in the mid-thirteenth century.